God as a Secure Base: Attachment to God and Theological Exploration - Beck, Richard (Journal of psychology and theology, 2006)
This study was an attempt to determine if God might provide a secure base for theological exploration. It was predicted that those displaying secure attachment with God would be more willing to “explore” their theological “world.” Participants were 117 undergraduate students who completed measures of attachment to God, Quest religious motives, and Christian orthodoxy. Overall, the study supported the experimental predictions. Specifically, the participants in the study who saw God as a “Secure Base” were more engaged in theological exploration and were more tolerant of Christian faiths different from their own. These same subjects also reported more peace and less distress during their spiritual journey. Yet, despite their exploration, these participants fully embraced the core doctrines of Christianity. Overall, these results suggest that the attachment paradigm might significantly illuminate research involving religious maturity, apostasy, and religious intolerance.